Effects of activated complements on platelets - Sa Ya-Lian; Huang Shou-Jian (Acta Pharmacologica Sinica, 2016)
AIM: To observe the effects of activation of complements on platelets and subsequently on vascular endothelial cells (VEC) and vascular smooth muscle cells (VSMC). METHODS: Zymosan A-induced morphological change of platelets was determined with an aggregometer, and prothrombinase expression was quantified using chromogenic substrate. Supernatant of zymosan A-treated platelet rich plasma (PRP) was added to the cultured VEC or VSMC for the observation of cell growth, DNA content, and the membrane microviscosity. RESULTS: Zymosan A induced marked metamorphosis, increased membrane microviscosity, and increased prothrombinase expression of platelets in PRP, but platelet metamorphosis induced by zymosan A was not found in washed platelets and fresh platelet suspended in platelet poor plasma (PPP) which had been pretreated with cobra venom factor (CVF). The effect of zymosan A on platelets was prevented by egtazic acid 5 mmol/L, Mn2+ 10 mmol/L, tetrodotoxin 40 micromol/L or indomethacin 100 micromol/L. The supernatant of zymosan A-treated PRP inhibited the growth of VEC, but accelerated the growth of VSMC and made most VSMC enter G2- and M- phase. The endoplasmic reticulum with rough surface and free ribosome in VSMC and vacuoles appeared in VEC mitochondria. CONCLUSION: Activated complements induced significant shape change of platelets, stimulated platelets to release some factors and subsequently injured VEC, but accelerated the growth of VSMC, which may contribute to the development of blood coagulation and to the chronic inflammation.